2021
DOI: 10.3389/fnins.2021.618435
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Quantitative Susceptibility Mapping (QSM) of Brain Iron Profile in Neurodegenerative Diseases

Abstract: Iron has been increasingly implicated in the pathology of neurodegenerative diseases. In the past decade, development of the new magnetic resonance imaging technique, quantitative susceptibility mapping (QSM), has enabled for the more comprehensive investigation of iron distribution in the brain. The aim of this systematic review was to provide a synthesis of the findings from existing QSM studies in neurodegenerative diseases. We identified 80 records by searching MEDLINE, Embase, Scopus, and PsycInfo databas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
134
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(144 citation statements)
references
References 162 publications
(146 reference statements)
9
134
0
1
Order By: Relevance
“…These histological and stain findings, which are characteristic of Zr skin lesions and granulomas, suggest Zr interstitial lung disease. Researchers (e.g., Cabral Pinto, et al, 2019; Mezzaroba, et al, 2019; Martins, et al, 2020; Soares, et al, 2020; Ajsuvakova, et al, 2020; Exley & Clarkson, 2020; McDonald, et al, 2021; Xu et al, 2021; Capriello, et al, 2021; Ravanfar, et al, 2021)) are working on exposure of other (heavy) metal (e.g., Al, Fe, and Mn) linked to neurological disorders and diseases, such Alzheimer and Parkinson diseases. The map distribution of HI is presented in Figure 6, with all samples above the target value of 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These histological and stain findings, which are characteristic of Zr skin lesions and granulomas, suggest Zr interstitial lung disease. Researchers (e.g., Cabral Pinto, et al, 2019; Mezzaroba, et al, 2019; Martins, et al, 2020; Soares, et al, 2020; Ajsuvakova, et al, 2020; Exley & Clarkson, 2020; McDonald, et al, 2021; Xu et al, 2021; Capriello, et al, 2021; Ravanfar, et al, 2021)) are working on exposure of other (heavy) metal (e.g., Al, Fe, and Mn) linked to neurological disorders and diseases, such Alzheimer and Parkinson diseases. The map distribution of HI is presented in Figure 6, with all samples above the target value of 1.…”
Section: Resultsmentioning
confidence: 99%
“…Liu, et al (2017) described a nonsmoking ceramic tile worker who developed a sarcoid granulomatosis type of chronic pulmonary hypersensitivity reaction after long-term exposure to Zr and causes an acute and fulminant allergic alveolitis. Romeu, et al (1992) found interstitial lung Pinto, et al, 2019;Mezzaroba, et al, 2019;Martins, et al, 2020;Soares, et al, 2020;Ajsuvakova, et al, 2020;Exley & Clarkson, 2020;McDonald, et al, 2021;Xu et al, 2021;Capriello, et al, 2021;Ravanfar, et al, 2021)) are working on exposure of other (heavy) metal (e.g., Al, Fe, and Mn) linked to neurological disorders and diseases, such Alzheimer and Parkinson diseases. The map distribution of HI is presented in Figure 6, with all samples above the target value of 1.…”
Section: Spatial Variation Of Ecological and Human Risksmentioning
confidence: 99%
“…These methods have proven particularly useful to differentiate clinical phenotypes and map longitudinal changes in neurodegenerative disorders (7,271). Novel MRI pulse sequences, non-Gaussian diffusion models such as DKI or NODDI, quantitative susceptibility mapping, and multi-voxel spectroscopy are just some of the promising new tools enriching our armamentarium of imaging tools (272)(273)(274). While these methods continue to be tested in the research community they have not been implemented in routine clinical radiology protocols (275).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence also suggests the role of excess iron deposition in the pathology of neurodegenerative diseases. Quantitative susceptibility mapping is a promising imaging technique for the comprehensive investigation of iron distribution in the brain [ 152 ]. The use of the diffusion tensor-relaxometry framework or combining advanced diffusion MRI techniques and quantitative susceptibility mapping might provide a more comprehensive picture of neurodegenerative diseases by analyzing different biological tissue properties.…”
Section: Discussionmentioning
confidence: 99%